RP-HPLC Method Development and Validation for Estimation of Acebrophylline - Sharma, Bhavik,; Agarwal, Sushil Kumar (Asian Journal of Pharmaceutical Research and Development, 2019)
Acebrophylline is an anti-inflammatory and airway mucus regulator. It had ambroxol and theophylline-7-acetic acid, the former facilitates the biosynthesis of pulmonary surfactant which raises blood levels of ambroxol, by stimulating surfactant production. Chemical structure of acebrophylline is 1, 2, 3, 6- tetrahydro-1, 3-dimethyl-2, 6-dioxo-7H-purine-7-aceticacidwithtrans-4-[(2-amino-3, 5 dibromophenyl) methyl] aminio] cyclohexanol. Survey revealed that various analytical methods like spectrophotometric, HPLC, and RP-HPLC, have been reported for the determination of Ambroxol HCl and Theophylline-7-acetic acid, individually and in combination with some other drugs. The aim of present study was to develop and validate stability indicating HPLC method for the analyses of acebrophylline. High performance liquid chromatographic method has been developed for the estimation of Acebrophylline. Reported methods also include RP-HPLC method for determination of Acebrophylline. The developed UV spectrophotometric method is simple and requires less time for the analysis. It is also rapid and economic method.